ANALISIS HUBUNGAN EMPATI SISWA DENGAN MOTIVASI BELAJAR IPA PADA PEMBELAJARAN DI MASA PANDEMI - Anggraini, Erika Putri; Muharrami, Laila Khamsaatul; Rosidi, Irsad (Program Studi Pendidikan IPA, Universitas Trunojoyo Madura, 2023)
The aims of the research were to know of the form of empathy, the percentage and the relationship between students' empathy with science learning motivation towards learning. The research used a mix method and was conducted at SMPN 3 Waru. The population was seven-grade students in the academy year of 2020/2021. Sample selection through purposive sampling technique. the sampling of this research is VII-I class. Data collection through observation, test, interviews, and documentation. Questionnaire is collected online through google form while the interviews were conducted in person. The results showed the empathy in the form of: 1) being sensitive to others, 2) trusting others, 3) understanding others, 4) awareness of others, 5) openness, 6) sosial contact 7) sosial community. The average percentage of empathy for students in grades VII-I of SMPN 3 Waru is in the high category with a percentage of 76.3%. Students' empathy affects the motivation to learn science and affects learning..